Familial partial 7q monosomy resulting from segregation of an insertional chromosome rearrangement. - Nielsen, K B (1979)
A family with an insertional type of chromosome rearrangement involving chromosomes 7 and 13 is reported. An interstitial deletion of a segment of chromosome 7 (7q32 leads to 34) had been inserted into the long arm of chromosome 13 at breakpoint q32. Segregation of this chromosome rearrangement gave rise to three subjects who were monosomic for the involved segment of chromosome 7. The karyotypes were: 46,XX, or XY,der(7)ins(13;7) (q32;q32q34). All three subjects were mentally retarded and had minor dysmorphic features. The Kidd, Colton, and Kell blood group systems were investigated, but were not informative.